Antioxidant Activity of Methanolic Extracts of Borago Officinalis, Teucrium Polium, Mentha Aquatica and Allium Taradox - Shahdadi , Fatemeh; Salehi Sardoei, Ali (Archives of Medical Laboratory Sciences, 2023)
Background and Aim: Free radicals and the oxidative stress they generate are implicated in a wide range of disorders in the human body. One of the important approaches to eliminate free radicals and prevent their side effects is to use natural antioxidants. Plants contain significant amounts of phenolic compounds in all their parts that give them antioxidant properties. This study aims to evaluate the antioxidant activity and phenolic content of methanolic extracts from aerial parts of some medicinal plants. Methods: Methanolic extracts from the leaves of Wild Borage (Borago officinalis), Teucrium (Teucrium polium), Water Mint (Mentha aquatica) and Wild Leek (Allium taradox) were prepared and evaluated for their free-radical scavenging capacity or their antioxidant activity. The amount of total phenolic content was determined using the folin-ciocalteu method and the amount of anti - radical activity was determined using the DPPH free radical scavenging method and determining inhibitory concentration (IC50). All experiments were performed in triplicate. Results: The obtained results and statistical analyses showed that the methanolic extracts of Borago officinalis and Teucrium polium contain high amounts of phenolic compounds and also had more free radical inhibition due to the lower IC50 values. Also, Borago officinalis had significant antioxidant activity compared to other plants. Conclusion: Our investigation indicates that Borago officinalis leaves are a promising source of natural antioxidants. *Corresponding Author: Ali Salehi Sardoei; Email: Alisalehisardoei@gau.ac.ir; ORCID ID: 0000-0002-4054-3750 Please cite this article as: Shahdadi F, Salehi Sardoei A. Free Radical Scavenging Capacity and Antioxidant Activity of Methanolic Extracts of Borago Officinalis, Teucrium Polium, Mentha Aquatica and Allium Taradox. Arch Med Lab Sci. 2023;9:1-7 (e4). https://doi.org/10.22037/amls.v9.38310